Influence of culverts on frost depth in embankments: a field study - Tommik, Karina; Knutsson, Sven; Laue, Jan (Luleå tekniska universitet, Geoteknologi, 2024)
Frost-related damages around culverts are a common problem for roads and railways built on seasonally frozen ground. Culverts create altered thermal conditions in the embankment section where they are installed, leading to deeper frost penetration around the culverts compared to the rest of the road. However, estimating the depth of frost penetration and consequential heave is difficult due to the complex thermal conditions inside culverts, which depend on various factors. To monitor the influence of culverts on the surrounding soil and assess the effect of temperature distribution inside the culvert on frost penetration in the embankment, temperatures were measured inside a 0.6 m diameter culvert and in the soil 0.30 m from the culvert in northern Sweden during the winter of 2023. Control measurements were also performed in a road section without a culvert. Temperatures were recorded in seven locations in the embankment at depths ranging from 0.1 m to 2.55 m. Effect of the temperature distribution inside the culvert on frost penetration in the embankment is assessed. The results of this study could help in the design and management of culverts in cold climates and improve our understanding of the thermal conditions around culverts. This field study is part of a larger project where collected data will be used to verify numerical models, enabling assessment of the effect of culverts of any size on temperature distribution. ISBN for host publication: 9781003431749, 978-1-032-54816-6; Full text license: CC BY-NC-ND